Kepemimpinan Transformasional sebagai Anteseden Sinisisme terhadap Perubahan Organisasional - Zona, Mega Asri (Jurnal Kajian Manajemen Bisnis, 2016)
This research used transformational leadership as independent variable to cynicism about organizational change. Transformational leadership expected to has negatif and significant influence on cynicism about organizational change. Survey conducted to 250 employees at PT. PLN Padang (Rayon Kuranji, Rayon Tabing, Rayon Belanti, and Rayon Indarung), PT. Telkom Padang, PT. MNC Sky Vision (KPP Padang and KPP Bukittinggi). Data analyzed using moderated regression analysis.The research finding showed that transformational leadership had negative and significant effect on cynicism about organizational change.